ON THE ISSUE OF “MIXED” CERAMIC COMPLEXES IN THE NEOLITHIC MIDDLE IRTYSH RIVER REGION AND BARABA - A. Yu. Yurakova (Вестник Кемеровского государственного университета, 2015)
The paper deals with historiographical traditions of detecting and interpreting the ceramic complexes with ‘mixed’ characteristics within the periodization diagrams. The author analyses the validity and possible criteria of determining such facts and describes the main issues related to Comb-Pit and Artyn complexes in the Neolithic Middle Irtysh River region and Baraba.